Collaborative computing : networking, applications and worksharing : 15th EAI International Conference, CollaborateCom 2019, London, UK, August 19-22, 2019, Proceedings /: networking, applications and worksharing : 15th EAI International Conference, CollaborateCom 2019, London, UK, August 19-22, 2019, Proceedings. (2019) - Unknown
No abstract available